Jackie Howes and two other women - Unknown:::Creator::::::::::::
Photograph shows Jackie Howes with two other women standing with poster-sized building plans. Jackie is pointing to an area on the plan for the first floor. The plans on the bottom of the poster are for the first floor and the top of the poster has plans for the second through the sixth floors.